Potensi Bakteri Endofit dari Akar Kecombrang (Etlingera elatior (Jack) R. M. Smith) dalam Menghambat Pertumbuhan Staphylococcus aureus - Lubis, Nurul Abdillah; Nurtjahja, Kiki; Rahmiati, Rahmiati; Susilo, Ferdinand (Universitas Medan Area, 2024)
Endophytic bacteria are bacteria that live within plant tissues and are capable of producing secondary metabolites in the form of bioactive compounds similar to those produced by their host plants. This study aims to isolate and characterize endophytic bacteria from the roots of kecombrang (Etlingera elatior (Jack) R. M. Smith) and to test their ability to inhibit the growth of Staphylococcus aureus. The research was conducted using a quantitative descriptive method through several stages, including sample preparation, sterilization of equipment and media, isolation, characterization, and testing. The results identified three isolates of endophytic bacteria from the roots of kecombrang, namely AK1, AK2, and AK3, which were shown to be gram-positive cocci. Inhibition tests indicated that these endophytic bacteria exhibit antagonistic properties against Staphylococcus aureus. The isolate coded AK1 had an inhibition zone of 9.6 mm, AK2 had the lowest inhibition zone of 6.6 mm, and AK3 had the largest inhibition zone of 13.5 mm.